If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(2x+3)+2=-3(2x+7)+2x
We move all terms to the left:
-2(2x+3)+2-(-3(2x+7)+2x)=0
We multiply parentheses
-4x-(-3(2x+7)+2x)-6+2=0
We calculate terms in parentheses: -(-3(2x+7)+2x), so:We add all the numbers together, and all the variables
-3(2x+7)+2x
We add all the numbers together, and all the variables
2x-3(2x+7)
We multiply parentheses
2x-6x-21
We add all the numbers together, and all the variables
-4x-21
Back to the equation:
-(-4x-21)
-4x-(-4x-21)-4=0
We get rid of parentheses
-4x+4x+21-4=0
We add all the numbers together, and all the variables
17!=0
There is no solution for this equation
| y=1/4*12-10 | | (5x–23)-(3x–4)=9 | | 3x-5(x-4)=-5=4x-17 | | (6x+7)+(6x-17)=180 | | 1/12(x-40)=4+x | | 41=3r-13 | | h-47=83 | | 3n/8+n/2=7 | | -5x+11=-39 | | (3m•2)+2m=102 | | 2x²-6x=360 | | 6t+8=20 | | X-2=4-3x | | 3(x+5)=-4x+5 | | 9^(n+2)=27 | | -7v+4(v+3)=9 | | -4.7x=-9.4 | | 90+2y+5=5*21.4-17 | | 6-21/4=21/2+b | | q-33/7=9 | | 14=-7f-9 | | 102x+4=4x+5 | | -x^2-2x-7=×-6 | | 4b=2A-6 | | 12=-9-p | | 4(p+10)=88 | | 8x-4(0)=18 | | 90-(15+b+1.5(b+2)+2b-9)=b | | x–2=4–3x | | 3/5s-7/4=s/8+3/4 | | (7x-11)(5x-2)(2x-3)=180 | | 76=31+3p |